Malicious cryptography exposing cryptovirology - Young, Adam 1972-; Yung, Moti (Wiley Publishing, 2004)
Annotation
Includes bibliographical references and index. - Print version record
Keywords: Computer security; Cryptography; Computer viruses -- Prevention; Data protection; Sécurité informatique; Cryptographie; Protection de l'information (Informatique); Computer viruses; Prevention